Industrial relations in the Caribbean issues and perspectives - Goolsarran, Samuel J. (ILO-Caribbean Port of SpainTT, 2006)
Presents a general perspective and overview of industrial relations and looks at the role of stakeholders, social partners and relevant labour institutions and agencies. Reflects on labour laws and regulations and reviews procedures from the voluntary self-regulation to compulsory means for the institutional management of the system of industrial relations.